2012
DOI: 10.3109/10428194.2012.729057
|View full text |Cite
|
Sign up to set email alerts
|

Micafungin as empirical antifungal therapy in hematological patients: a retrospective, multicenter study in the Czech and Slovak Republics

Abstract: The objective of this retrospective, multicenter study was to evaluate the efficacy and safety of micafungin as empirical antifungal therapy during febrile neutropenia (FN) in 73 hematological patients from six centers in two countries. All patients received 100 mg of micafungin/day. The overall favorable response rate (RR) was 64.8% when the resolution of fever during neutropenia was included in the response criteria and 84.5% when excluded. A significantly lower favorable RR in patients with persistent fever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…However, the results of this study suggest that micafungin is well-tolerated in patients with hepatic impairment and may be suitable as an alternative to anidulafungin. The results from the present real-life study support the favourable safety profile of micafungin observed in previous studies [17,[35][36][37][38][39][40][41][42][43].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the results of this study suggest that micafungin is well-tolerated in patients with hepatic impairment and may be suitable as an alternative to anidulafungin. The results from the present real-life study support the favourable safety profile of micafungin observed in previous studies [17,[35][36][37][38][39][40][41][42][43].…”
Section: Discussionsupporting
confidence: 90%
“…More than half of patients with a recorded indication of esophageal candidiasis received a lower daily dose of micafungin than recommended in the product information and treatment guidelines [15,18]. Prophylaxis with 100 mg day −1 for some patients in Slovenia was selected based on data from a previous study in which this dose was well-tolerated [38]. In addition, guidelines from the Infectious Diseases Society of America recommend 100 mg day −1 for prophylaxis of IC in the ICU setting; however, this is a weak recommendation with low-quality evidence [15].…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis of IFD is often difficult, and sometimes the only clinical indication for its presence is isolated persistent fever in patients receiving broad-spectrum antibiotics together with subsequent non-specific pulmonary infiltrates on high-resolution computed tomography, without any microbiological documentation of its aetiology [1]. The autopsy data also revealed that 45% of patients with proven aspergillosis had repeatedly negative galactomannan test results prior to death – thus underscoring the importance of autopsy evidence for evaluating the performance of new diagnostic tests [4].…”
Section: Discussionmentioning
confidence: 99%
“…Identification of patients at risk is crucial for improvement of antifungal treatment results. Progress in anti-neoplastic treatment, and the use of aggressive chemotherapy and new drugs affecting the immune system have rapidly expanded the patient populations predisposed to IFD development [14]. …”
Section: Introductionmentioning
confidence: 99%
“…HEPA filters may not completely prevent IFI in high-risk patients [ 16 ]. As a result, antifungal prophylaxis should be considered as another preventive option in high-risk patient groups [ 6 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%